Artificial orpiment, a new pigment in Rembrandt’s palette - van Loon, Annelies; Noble, Petria; Krekeler, Anna; Van der Snickt, Geert; Janssens, Koen; Abe, Yoshinari; Nakai, Izumi; Dik, Joris (Heritage science, 2017)
This paper reports on how the application of macro X-ray fluorescence (MA-XRF) imaging, in combination with the re-examination of existing paint cross-sections, has led to the discovery of a new pigment in Rembrandt’s palette: artificial orpiment. In the NWO Science4Arts ‘ReVisRembrandt’ project, novel chemical imaging techniques are being developed and applied to the study of Rembrandt’s late paintings in order to help resolve outstanding questions and to gain a better understanding of his late enigmatic painting technique. One of the selected case studies is the Portrait of a Couple as Isaac and Rebecca, known as ‘The Jewish Bride’, dated c. 1665 and on view in the Rijksmuseum. During the re-installation of the Rijksmuseum in 2013, the picture was scanned using the Bruker M6 Jetstream MA-XRF scanner. The resulting elemental distribution maps made it possible to distinguish many features in the painting, such as bone black remains of the original hat (P, Ca maps), and the now discolored smalt-rich background (Co, Ni, As, K maps). The arsenic (As) map also revealed areas of high-intensity in Isaac’s sleeve and Rebecca’s dress where it could be established that it was not related with the pigment smalt that also contains arsenic. This pointed to the presence of a yellow or orange arsenic-containing pigment, such as realgar or orpiment that is not associated with the artist’s palette. Subsequent examination of existing paint cross-sections from these locations taken by Karin Groen in the 1990s identified isolated, almost perfectly round particles of arsenic sulfide. The round shape corresponds with published findings on a purified form of artificial orpiment glass obtained by dry processing, a sublimation reaction. In bright field, the particles characteristically exhibit a dark cross in the middle caused by internal light reflections. The results of additional non-invasive techniques (portable XRD and portable Raman) are discussed, as well as the implications of this finding and how it fits with Rembrandt’s late experimental painting technique.